Association of Ozone Exposure With Cardiorespiratory Pathophysiologic Mechanisms in Healthy Adults - Day, D. B.; Xiang, J.; Mo, J.; Li, F.; Chung, M.; Gong, J.; Weschler, C. J.; Ohman-Strickland, P. A.; Sundell, J.; Weng, W.; Y. Zhang; J.J. Zhang (JAMA Intern Med, 2017)
Importance: Exposure to ozone has been associated with cardiovascular mortality, but the underlying biological mechanisms are not yet understood. Objective: To examine the association between ozone exposure and cardiopulmonary pathophysiologic mechanisms. Design, Setting, and Participants: A longitudinal study involving 89 healthy adult participants living on a work campus in Changsha City, China, was conducted from December 1, 2014, to January 31, 2015. This unique quasiexperimental setting allowed for better characterization of air pollutant exposure effects because the participants spent most of their time in controlled indoor environments. Concentrations of indoor and outdoor ozone, along with the copollutants particulate matter, nitrogen dioxide, and sulfur dioxide, were monitored throughout the study period and then combined with time-activity information and filtration conditions of each residence and office to estimate 24-hour and 2-week combined indoor and outdoor mean exposure concentrations. Associations between each exposure measure and outcome measure were analyzed using single-pollutant and 2-pollutant linear mixed models controlling for ambient temperature, secondhand smoke exposure, and personal-level time-varying covariates. Main Outcomes and Measures: Biomarkers indicative of inflammation and oxidative stress, arterial stiffness, blood pressure, thrombotic factors, and spirometry were measured at 4 sessions. Results: Of the 89 participants, 25 (28%) were women and the mean (SD) age was 31.5 (7.6) years. The 24-hour ozone exposure concentrations ranged from 1.4 to 19.4 parts per billion (ppb), corresponding to outdoor concentrations ranging from 4.3 to 47.9 ppb. Within this range, in models controlling for a second copollutant and other potential confounders, a 10-ppb increase in 24-hour ozone was associated with mean increases of 36.3% (95% CI, 29.9%-43.0%) in the level of platelet activation marker soluble P-selectin, 2.8% (95% CI, 0.6%-5.1%) in diastolic blood pressure, 18.1% (95% CI, 4.5%-33.5%) in pulmonary inflammation markers fractional exhaled nitric oxide, and 31.0% (95% CI, 0.2%-71.1%) in exhaled breath condensate nitrite and nitrate as well as a -9.5% (95% CI, -17.7% to -1.4%) decrease in arterial stiffness marker augmentation index. A 10-ppb increase in 2-week ozone was associated with increases of 61.1% (95% CI, 37.8%-88.2%) in soluble P-selectin level and 126.2% (95% CI, 12.1%-356.2%) in exhaled breath condensate nitrite and nitrate level. Other measured biomarkers, including spirometry, showed no significant associations with either 24-hour ozone or 2-week ozone exposures. Conclusions and Relevance: Short-term ozone exposure at levels not associated with lung function changes was associated with platelet activation and blood pressure increases, suggesting a possible mechanism by which ozone may affect cardiovascular health.
Keywords: *Cardiovascular Diseases/diagnosis/epidemiology/metabolism/physiopathology; *Environmental Exposure/adverse effects/analysis/prevention & control; *Ozone/adverse effects/analysis; *Pneumonia/diagnosis/epidemiology/metabolism/physiopathology; Adult; Air Pollution/adverse effects/analysis/prevention & control; Breath Tests/methods; China/epidemiology; Female; Humans; Male; Nitrates/*analysis; Nitrites/*analysis; Nitrogen Dioxide; Oxidative Stress; Prothrombin Time/methods; Spirometry/methods; Vascular Stiffness